Full-Stack React Projects : Modern web development using React 16, Node, Express, and MongoDB. - Komanduri, Sai Kishore (Packt Publishing, 2018)
Combining React with industry tested server-side technologies such as Node, Express, and MongoDB creates a diverse array of possibilities when developing real-world web applications. This book guides you through setting up for MERN-based web development to building social media, an online marketplace, media streaming, and VR-infused game ...